Screening: Pelatihan dan Pendampingan Evaluasi Hasil Belajar Berbasis ICT Bagi Guru Akuntansi SMK di Kota Malang - Slamet , Slamet; Sunaryanto, Sunaryanto; Putri, Dhika Maha (Dharma: Jurnal Pengabdian Masyarakat, 2021)
This service aims to provide training and assistance to SMK Accounting Teachers in Malang City in evaluating learning outcomes. This activity is carried out by utilizing a screening application based on Ms. Excel. This is motivated because the process of evaluating student learning outcomes based on the final score and its implementation is still manual. Even though the era of industrial revolution 4.0 requires teachers to develop learning with technology. The result of this service is the Ms. Excel-based screening application training to evaluate student learning outcomes per Basic Competence. Thus, student learning outcomes will be seen per Basic Competence and the teacher can find out which parts have not been understood by students. The success of this service was measured by the percentage of understanding of the use of ICT, which rose from 55% before the training to 75% after the training.